Family as the Center of Education According to Ki Hajar Dewantara - Nila Frischa Panzola; Herman Nirwana; Dina Sukma (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Education in the family is the main foundation for the formation of children's character and intelligence. This article discusses the application of Ki Hadjar Dewantara's educational methods in the family context, emphasizing the importance of the role of parents as primary educators. The family environment is the initial educational environment for every individual because that is where the first education provided by parents, whose position as teacher (guide), lecturer and work leader (example), is very relevant for creating a conducive learning environment at home. Instilling moral and ethical values, direct experience-based learning, and developing children's creativity and independence are methods that can be applied by parents. This article also identifies the challenges families face in the modern era and offers practical solutions to overcome these challenges. With a better understanding of Ki Hadjar Dewantara's educational concept, it is hoped that families can educate their children to become individuals with integrity, intelligence and noble character.